2018
DOI: 10.1097/md.0000000000011569
|View full text |Cite|
|
Sign up to set email alerts
|

A network meta-analysis of nonsmall-cell lung cancer patients with an activating EGFR mutation

Abstract: Background:Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are the preferred first-line treatment for nonsmall-cell lung cancer (NSCLC) patients with an activating EGFR mutation. Osimertinib, compared with erlotinib or gefitinib, showed an improvement in progression-free survival (PFS) in a recent trial. The authors compared EGFR TKIs in terms of PFS in a network meta-analysis.Methods:The PubMed and Embase databases and meeting abstracts were screened for relevant studies between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 39 publications
(52 reference statements)
0
29
0
Order By: Relevance
“…In comparison to other published NMAs, this NMA included more trials and thus had a bigger sample size. Additionally, a NMA published in 2018 only reported PFS as efficacy outcome and did not report any ORR or OS results, while all outcomes were included in this NMA [ 40 ]. Erlotinib and gefitinib were combined in one arm in the previously published NMA, while they were analyzed separately in this NMA [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to other published NMAs, this NMA included more trials and thus had a bigger sample size. Additionally, a NMA published in 2018 only reported PFS as efficacy outcome and did not report any ORR or OS results, while all outcomes were included in this NMA [ 40 ]. Erlotinib and gefitinib were combined in one arm in the previously published NMA, while they were analyzed separately in this NMA [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a NMA published in 2018 only reported PFS as efficacy outcome and did not report any ORR or OS results, while all outcomes were included in this NMA [ 40 ]. Erlotinib and gefitinib were combined in one arm in the previously published NMA, while they were analyzed separately in this NMA [ 40 ]. Further, only the PFS ranking scores were reported in the previously published article [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RR (95% CI) for ORR and HR (95% CI) for PFS were 1.05 (1.00-1.11) and 1.00 (0.95-1.04), respectively [20]. Another network meta-analysis of 11 clinical trials also showed the similar PFS between gefitinib and erlotinib [21]. However, unlike our findings, the third-generation EGFR inhibitor osimertinib was found to have a longer PFS (HR 0.71, 95% CI 0.54-0.95), and the significant difference between the second-generation EGFR inhibitor afatinib and standard of care (either gefitinib or erlotinib) was not observed (HR 0.96, 95% CI, 0.86-1.17) [21].…”
Section: Comparison With Previous Studiesmentioning
confidence: 93%
“…Moreover, the FLAURA study demonstrated that osimertinib was more effective in improving PFS as a first-line treatment for EGFR mutation-positive advanced NSCLC compared to standard EGFR-TKIs (gefitinib or erlotinib) with a similar safety profile and lower rates of serious adverse events [ 100 ]. A recent network meta-analysis (NMA) revealed that osimertinib was the best therapeutic agent among five major EGFR TKIs as first-line treatments because it achieved the longest PFS of patients with NSCLC containing EGFR -activating mutations [ 101 ]. We performed a NMA using the statistical method of the frequentist approach [ 102 ] to evaluate four phase III trials [ 100 , 103 , 104 , 105 ] including 1305 patients for PFS to examine first-line treatment of NSCLC with EGFR -activating mutations.…”
Section: Egfr Targeted Cancer Therapy Resistance and Overcoming Rementioning
confidence: 99%